Estudio fitoquímico de Pistacia mexicana - Rodríguez López, Fidel (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Hexane extracts were obtained from the fruits and stems of Pistacia mexicana, from which β-sitosterol (1) and masticadienonic acid (2) were isolated, obtaining the latter in significant quantities. Using 2 as starting material, esters 13 and 14 were synthesized, using diazomethane and CDI as a reagent for carbonyl group activation, respectively. Derivatives 15 and 16 were also prepared by a reductive treatment of 2 and 13 with NaBH4. From 15, derivatives 17 and 18 were prepared by acylation of the hydroxyl group in C-3 with acid anhydrides and acid chlorides respectively. Finally, α-acyloxyamides 19-22 were synthesized using 2 as the acid component of Passerini multicomponent reaction, and t-butylisocyanide and aliphatic and aromatic aldehydes with electron donor and withdrawing groups as the other two components of the reaction.

A partir de los frutos y tallos de Pistacia mexicana se obtuvieron los extractos hexánicos, de los cuales se logró el aislamiento del β-sitosterol (1) y el ácido masticadienónico (2) logrando obtener este último en cantidades significativas. Utilizando 2 como materia prima, se sintetizaron los ésteres 13 y 14 utilizando diazometano y la activación de grupos carbonilo con CDI, respectivamente. Se prepararon también los derivados 15 y 16, mediante la reducción con NaBH4 de 2 y 13 y se obtuvieron derivados 17 y 18, mediante acilaciones del grupo hidroxilo en C-3 con anhídridos de ácido y cloruros de ácido respectivamente. Finalmente, empleando 2 como componente ácido de la reacción de multicomponentes de Passerini, se lograron sintetizar las α-aciloxiamidas 19, 20, 21 y 22, utilizando como reactivos t-butilisonitrilo y una serie de aldehídos alifáticos y aromáticos con grupos electroatractores y electrodonadores.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-R-M-2020-0203; Triterpeno; CDI; RMC; Passerini; α-aciloxiamida; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2318